Study on Stone Blocks Used for Resthouses Along the Northwest Royal Road Connecting Angkor in Cambodia and Phimai in Thailand Based on On-Site Magnetic Susceptibility Measurements and Chemical Composition Analyses - Etsuo Uchida; Yoshimitsu Kobayashi; Aoi Mizumori; Kaito Kuriyama; Keishiro Azami (Heritage)
The purpose of this paper was to identify the types of stone used in the “Resthouses” along the Northwest Royal Road connecting Angkor in Cambodia and Phimai in Thailand and to determine their sources through magnetic susceptibility measurements and chemical composition analyses. Laterite was the primary building material for the “Resthouses”, except for Pr. Ku Sila Khan in Thailand. Pr. Ku Sila Khan, located at the northernmost point of the Northwest Royal Road, was primarily built with fine-grained red sandstone. Based on the magnetic susceptibility and the V, Sr, and As contents of the laterite, the following pairs of “Resthouses” were likely sourced from the same quarries: Pr. Sampov and Pr. Saman Teng, Pr. Kok Ac Chring and Pr. Kok Mon, Pr. Ta Muan and Pr. Thamo, and Pr. Ban Bu and Pr. Non Kong. Fine-grained red sandstone, white siliceous sandstone, red siliceous sandstone, and gray sandstone were used for the frame material of the openings. The Rb vs. Ti diagram and magnetic susceptibility measurements suggest that the fine-grained red sandstone and siliceous white sandstone used in the “Resthouses” in Thailand were likely sourced from the Khok Kruat Formation and the Phu Phan Formation, respectively. However, the red siliceous sandstone and white siliceous sandstone used in the “Resthouses” in Cambodia are presumed to have been sourced from the Sao Khua Formation and the Phra Wihan Formation, respectively. Gray sandstone from the Phu Kradung Formation was uniquely used in the frame material of the openings of Pr. Sampov and Pr. Kok Mon in Cambodia. In conclusion, the sandstone used in the door and window frames of the “Resthouses” appears to have been determined by the surrounding geology. Laterite was used as the primary building material for the “Resthouses” along the Northwest Royal Road, whereas valuable sandstone was used for those along the East Royal Road. This suggests that the Northwest Royal Road was of lesser importance compared to the East Royal Road.